Tersembunyi di Balik Keramaian: Eksplorasi Sisi Lain Pasar Gede Hardjonagoro Kota Surakarta 1998-2001 - Noviana, Rinta Noviana (Journal of Indonesian History, 2023)
Pasar Gede Hardjonagoro or better known as Pasar Gede, is a market located in Surakarta City. Pasar Gede itself is included in the category of the golden triangle area which is included in a strategic area. Traders in this market come from various regions and also ethnicities. As one of the parent markets, Pasar Gede is not only used by traders. Many other parties play a role in it, such as porters. Its existence also celebrates market activity. Not only as a place to buy and sell, Pasar Gede is also a place that provides night entertainment. Markets with activities that are quite dense and open for 24 hours can be a crime target. The research aims to find out the other side of Pasar Gede which is rarely known to the general public. The method used is the historical research method. Data collection is done by searching for primary sources and secondary sources. Primary sources in can be from newspapers and interviews. Secondary sources are obtained from articles, theses and books. The results of this study show that people who work in Pasar Gede come from various ethnicities and have a harmonious relationship. Trading in Pasar Gede is not only crowded with buying and selling activities, but there is also interaction and cooperation carried out by porter, cleaners, and security. People who work in Pasar Gede come from various ethnicities and have a harmonious relationship. Keywords: Pasar Gede, Trader, Porter